Lemkin on Genocide - Lemkin, Raphael (2012)
Providing an annotated commentary on two unpublished manuscripts written by international law and genocide scholar Raphael Lemkin, Steven L. Jacobs offers a critical introduction to the father of genocide studies. Lemkin coined the term ""genocide"" and was the motivating force behind the 1948 United Nations Convention on the Punishment and Prevention of the Crime of Genocide. The materials collected here give readers further insight into this singularly courageous man and the issue which consumed him in the aftermath of the Second World War. It is a welcome addition to the library of genocide...